The Objective Structured Clinical Examination and student collusion: marks do not tell the whole truth. Issue 12 (4th December 2006) - Parks, R; Warren, P M; Boyd, K M; Cameron, H; Cumming, A; Lloyd-Jones, G
Abstract : Objective: To determine whether the marks in the third year Objective Structured Clinical Examination (OSCE) were affected by the collusion reported by the students themselves on an electronic discussion board. Design: A review of the student discussion, examiners' feedback and a comparison of the marks obtained on the 2 days of the OSCE. Participants: 255 third year medical students. Setting: An OSCE consisting of 15 stations, administered on three sites over 2 days at a UK medical school. Results: 40 students contributed to the discussion on the electronic discussion board. The main points raised were perceived inequity between students who did, or did not, have prior knowledge of the station content, and the lack of honesty and professionalism of their peers. Most contributors claimed to have received, or knew of others receiving, prior knowledge, but none confessed to passing on information. No significant difference (p = 0.16) was observed in the overall mark for the OSCE on day 1 (mean 390 (SD 37)) and day 2 (mean 397 (38)). On day 2, marks were considerably greater for four stations and markedly lower for three stations. It was not obvious why collusion should affect these station marks. A clear indication of the effects of collusion could only be obtained from a single subsection of an individual station (pathology) where 82 students on day 2 incorrectly gave the diagnosis from day 1. Conclusion: Marks do not provide a sound inference of student collusion in an OSCE and may mask the aspects of professional development of students.